2001
DOI: 10.1159/000054707
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Thyrotropin-Releasing Hormone (TRH) Neurons to Cold Exposure or Suckling Indicate Functional Heterogeneity of the TRH System in the Paraventricular Nucleus of the Rat Hypothalamus

Abstract: Thyrotropin-releasing hormone (TRH) is released from the median eminence upon neural stimulation such as cold or suckling exposure. Concomitant with the cold- or suckling-induced release of TRH is a rapid and transient increase in the expression of proTRH mRNA in the paraventricular nucleus (PVN) of the hypothalamus. We employed two strategies to determine whether TRH neurons responding to cold exposure are different from those responding to suckling. First, we attempted to identify a marker of cellular activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 40 publications
3
60
2
1
Order By: Relevance
“…Accordingly, TRH may, in relation to nursing, modulate a number of CNS functions through activation of TRHR1 (65). The present findings extend previous observations of Uribe, Sanchez and colleagues (15,66) that showed that mRNA for proTRH was up-regulated in the PVN under a number of physiological conditions such as lactation and stress associated with freezing.…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, TRH may, in relation to nursing, modulate a number of CNS functions through activation of TRHR1 (65). The present findings extend previous observations of Uribe, Sanchez and colleagues (15,66) that showed that mRNA for proTRH was up-regulated in the PVN under a number of physiological conditions such as lactation and stress associated with freezing.…”
Section: Discussionsupporting
confidence: 89%
“…TRH gene expression in the PVN is strictly controlled by the feedback action of thyroid hormones (Koller et al 1987, Segerson et al 1987b, Rondel et al 1988, Hollenberg et al 1995, Satoh et al 1999 and is regulated in multiple physiological conditions including: circadian and estrous cycles (Covarrubias et al 1988, Uribe et al 1991, suckling and weaning (Uribe et al 1993, 1995b, Sánchez et al 2001, cold stress (Zoeller et al 1990, Uribe et al 1993, Sánchez et al 2001 and fasting (Blake et al 1991, Legradi et al 1997a, Fekete et al 2002. In addition, a fast and transient increase in proTRH mRNA levels in the PVN (maximal at 30-60 min) is produced by cold exposure or suckling (Uribe et al 1993, Sánchez et al 2001, conditions that activate TRH release from the median eminence (Arancibia et al 1983, de Greef et al 1987, Rondel et al 1988.…”
Section: Introductionmentioning
confidence: 99%
“…As CART is the only known peptide that coexists with TRH in the PVN (Fekete et al, 2000) it is feasible that under the appropriate circumstances, the genes for both peptides may become simultaneously activated. The paradigm of the lactating rat subject to either suckling or cold exposure, conditions when TRH neurons are rapidly activated in the PVN (Sánchez et al, 2001), exemplify in vivo situations where TRH is released but the secretion of TSH and prolactin diverge (Adels et al, 1986;Arancibia et al, 1983;de Greef and Visser, 1981;Sanchez et al, 2001;van Haasteren et al, 1996). Using this paradigm, we demonstrate herein a differential activation of CART neurons in the PVN, stimulated by cold exposure but not by suckling.…”
Section: Discussionmentioning
confidence: 63%
“…The rostral, mid, and caudal zones of the parvocellular PVN were identified by brightfield microscopic analysis of hematoxylin/eosin stained sections. Serial sections were hybridized with a 866-base pair single stranded [ 35 S] UTP labeled cRNA probe for CART (Couceyro et al, 1997) (kindly provided by Dr MJ Kuhar) and processed as previously described (Sanchez et al, 2001) except that final rinses were done in descending concentrations of SSC 2x, 1x, 0.5× and 0.1× at RT, two washes in 0.1× SSC for 30 min each at 60 °C and treatment with ascending concentrations of ethanol 75%, 80% and 95% for 2 min each. Specific labeling was detected with Kodak Bioma× film exposed for 7 days at room temperature.…”
Section: In Situ Hybridization Histochemistry (Ish)mentioning
confidence: 99%
See 1 more Smart Citation